Fuel subsidy rationalisation: the perils of the middle class in Malaysia - Roslan Abdul-Hakim; Russayani Ismail; Nor Azam Abdul-Razak (Penerbit Universiti Kebangsaan Malaysia, 2014)
The middle-class is reportedto experience the "middle-class squeeze", where they arefacing a decliningrelative income and simultaneously rising costs of living particularly with regards to housing, educqtion and health care. Besides, the middle-class is also reported to face "the middle-class trap", where on the one hand, they are regarded ai "too rich" to qualifi for any government support, but on the other hand, they found themselves in realily "not too rich" to sustain their lives withoutfacing hardships. These observations unfortunately seem to be equally true in Malaysia, which raises the need to scrutinise the likely impact of government policy on the middle-class. Iilith the recent fuel subsidy rationqlisation in Malaysia, this paper attempts to analyse the likely welfore impact of this policy towards the middle-class in the Malaysian society. Examining this issue is crucial and desirable since the problems faced by the middle-class tend to be overlooked by the policy makers. In our analysis, we use various definitions of "middle-class" as suggested in the literature, and examine the direct, indirect qnd the total welfare effects of fuel subsidy removal on them using data from the Household Expenditure Survey (HES) 2004/2005 as well as the Input-Output Table for 2004/2005. Ourfindings reveal that, in line with the common perception, the benefts offuel subsidy accrued mostly to the rich. Ironically, the costs of subsidy removal are borne mostly by the middle-class in terms of the direct effect. Yet in terms of the indirect welfare effect, the costs of subsidy removal are borne equally by the middle-class as well as the lower and the upper class. Since the indirect welfure effect outweighs the direct welfare effect, we conclude that while the rich get most of the benefitsfromfuel subsidy, its removal hurts the middle-class the most. Ourfnding implies that fuel subsidy rationalisation must befollowed by a practical strateglt and program to lessen the negative impact offuel subsidy removal not only for the poori but also for the middle-clqss as well.